2000
DOI: 10.1038/sj.ijo.0801354
|View full text |Cite
|
Sign up to set email alerts
|

The correlates of long-term weight loss: a group comparison study of obesity

Abstract: OBJECTIVE: Although the majority of weight loss attempts are unsuccessful, a small minority succeed in both weight loss and maintenance. The present study aimed to explore the correlates of this success. METHOD: A group comparison design was used to examine differences between women who were classi®ed as either weight loss maintainers (had been obese (body mass index, BMI 30 kgam 2 ) and had lost weight to be considered non-obese (BMI`30 kgam 2 ) and maintained this weight loss for a minimum of 3 y; n 44), sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 15 publications
5
36
0
Order By: Relevance
“…Previous research has explored patients' beliefs about the causes of obesity and suggests that whilst many patients prefer a more medical model (35) successful weight loss and maintenance is associated with a more psychological perspective (36). This was supported by the present study as all those who had not lost weight or regained any weight they had lost on orlistat focused on causes which were beyond their control involving genetics or illness (n=5).…”
Section: I)the Causes Of Their Obesitysupporting
confidence: 74%
“…Previous research has explored patients' beliefs about the causes of obesity and suggests that whilst many patients prefer a more medical model (35) successful weight loss and maintenance is associated with a more psychological perspective (36). This was supported by the present study as all those who had not lost weight or regained any weight they had lost on orlistat focused on causes which were beyond their control involving genetics or illness (n=5).…”
Section: I)the Causes Of Their Obesitysupporting
confidence: 74%
“…The results from the present study support such studies but suggest that an emphasis on behavior as central to both the cause and solution of a problem is also associated with behavior change that is sustained over time. This also refl ects previous research, which reported that a more psychological model of obesity was associated with weight loss maintenance (Ogden, 2000) but illustrates that such a model may also be relevant to health related behaviors in general.…”
Section: Behavioral Model Of Causes and Solutionsmentioning
confidence: 35%
“…This focus on success stories has been previously used to explore weight loss maintenance (e.g. Ogden, 2000;Elfhag and Rossner, 2005;Wing and Phelan, 2005) and enables the process of longer term change to be elicited from the person themself. The present study aimed to explore whether factors exist which relate to longer term changes in health behaviors in general and to explore the cognitions behind behavior change.…”
Section: Introductionmentioning
confidence: 99%
“…For example, research exploring adherence to asthma medication concluded that patients are more likely to take their medication if their beliefs about the cause of their problem are consistent with their beliefs about its treatment (Horne, 1997;Horne and Weinman, 1999;2002). Similarly, from a study of successful weight loss and maintenance, Ogden (2000) concluded that the 'success stories' were more likely to believe that behaviour was central to both the cause and 4 solution of their weight problem. Furthermore, consistent beliefs about causes and solutions have also been reported to relate to the effectiveness of weight loss medication (Ogden and Sidhu, 2006), uptake of rehabilitation following heart attack (Petrie et al, 1996) and sustained changes in diet, smoking and exercise behaviours (Ogden and Hills, in press).…”
Section: Introductionmentioning
confidence: 99%